ANALISIS PERHITUNGAN DAN PEMOTONGAN PPH PASAL 21 PADA KARYAWAN TETAP PT. MEGA JASAKELOLA MANADO - Dai, Rahmawaty A.; Ilat, Ventje; Mawikere, Lidia (Universitas Sam Ratulangi, 2018)
In accorrdance withh the Laaw no. 36 Year 2008, everyone should calculate the tax. Currently not a few companies that cut taxes that are not in accordance with applicable regulations. This is due to the company budgeted as a cost. The company will need a fee for profit. Therefore for the sake of smooth calculation and tax cuts required a god cooperatiion bettween the goverrnment anhd thee companny government. PT. Mega Jasakelola Manado is engaged in Security services (security), Cleaning Services (cleaning service) in Manado city especially in megamas area Manado, has provided security for the visitors mega mas Manado area. This study aims to determine the calculation and cutting income tax article 21 for employees of PT. Mega Jasakelola Manado is in compliance with applicable tax laws. This research uses descriptive method by digging company data, conducting and interviewing and testing the data by comparing the results of the company with the results of calculations obtained by the author. Data collected: payroll and calcullation and measurement off taax article 21 on employees of PT. Mega Jasakelola Manado 2017. Results obtained from the calcullation and withholding of incom tax articl 21 onn permanent employess of PT. Mega Jasakelola Manado is in conformity with the taxation laws No. 36 of 2008 and PMK no 101 / PMK.010 / 2016â€.Keywords: : Income tax, Tax, Taxpayer, taxation law, permanent employees